Regulatory Dynamics and Socio-Legal Impacts of Interfaith Marriages in Indonesia Post-SEMA Number 2 of 2023 - Priscilla Wijaya, Gabrielle; Hadiati, Mia (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Interfaith marriage in Indonesia ideally requires a clear and harmonious legal framework aligned with societal values and religious principles. However, in reality, the absence of explicit regulation in Law Number 1 of 1974 on Marriage has created legal uncertainty and social challenges, particularly prior to the issuance of SEMA Number 2 of 2023. This study aims to analyze the implementation of interfaith marriage regulations, their socio-legal impacts, and efforts to harmonize the legal framework in Indonesia. Using normative legal research methods with a juridical approach, this study is based on library research analysis. The findings reveal that SEMA Number 2 of 2023 has provided a clearer legal framework for the registration of interfaith marriages, although technical challenges persist. Socially, the regulation has shifted societal paradigms, while legally, it has increased legal certainty. Legal harmonization requires an integrated approach that considers legal pluralism, religious values, and the realities of Indonesian society.